Letter - Schevenels, Walther, b. 1894
026-0010-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe TELEGRAMS: INTERFED-PARIS TELEPHONE: INVALIDES 43-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA ENGLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY MEXICO NORWAY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President: W. M. Citrine, Great Britain Vice-Presidents: H. Jacobson, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R Tayerle, Czechoslovakia General Secretary: W. Schevenels Letter Sec. ref. div. No. 1122 24th August, 1939. Mr. H. V. Tewson, London. Dear Comrade Tewson, Thank you for your letter of the 18th August, informing us of the despatch of further consignments of clothing for Spanish refugees, for which we are very grateful. The necessary steps will be taken to arrange for the reception of these goods and their distribution. Yours sincerely, W. Schevenels, General Secretary: EAB 292/946/26/10